2020
DOI: 10.1002/mp.14139
|View full text |Cite
|
Sign up to set email alerts
|

Design of a focused collimator for proton therapy spot scanning using Monte Carlo methods

Abstract: Purpose: When designing a collimation system for pencil beam spot scanning proton therapy, a decision must be made whether or not to rotate, or focus, the collimator to match beamlet deflection as a function of off-axis distance. If the collimator is not focused, the beamlet shape and fluence will vary as a function of off-axis distance due to partial transmission through the collimator. In this work, we quantify the magnitude of these effects and propose a focused dynamic collimation system (DCS) for use in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The DCS has been the subject of several recent investigations about collimator design and potential use cases. From a design perspective, the placement of the collimators downstream of the range shifter reduces the lateral spread by 15% to 30%, compared to placing the collimators upstream of the range shifter [ 29 , 47 ]. Polyethylene was chosen as the range shifter material because it has the lowest scattering angle of all suitable plastics [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCS has been the subject of several recent investigations about collimator design and potential use cases. From a design perspective, the placement of the collimators downstream of the range shifter reduces the lateral spread by 15% to 30%, compared to placing the collimators upstream of the range shifter [ 29 , 47 ]. Polyethylene was chosen as the range shifter material because it has the lowest scattering angle of all suitable plastics [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conceptually, the DCS is a sliding-bar collimator that uses a common set of 3-cm-thick orthogonal trimmer blades placed downstream of an external 4-cm-thick polyethylene range shifter to intercept the proton beam as it scans near the target periphery [ 24 ]. To provide focused collimation, the DCS rotates the collimators to match the beam deflection angle as the collimators travel in a single plane, which can improve the lateral conformity [ 47 , 48 ]. By design, the DCS can effectively provide any aperture shape for all energy layers.…”
Section: Methodsmentioning
confidence: 99%
“…In this capacity, this work also serves as an experimental basis for the continued development of dynamic collimators, which has been the subject of recent focus for the DCS using Monte Carlo methods to design focused collimators. 28 Additionally, the activation of positron-emitting nuclides is also non-negligible and should be considered when designing the encapsulation of a clinical system. While the proposed prototype is not a clinically viable device, it has provided an opportunity to benchmark the work that has previously relied solely on Monte Carlo to parameterize asymmetric proton beamlets and investigate the potential challenges that face clinical implementation of a dynamic collimation system.…”
Section: Discussionmentioning
confidence: 99%
“…Progressively, the results from this work have shown the sensitivity of the component alignment and influences of spot deflection toward a non‐focused collimator. In this capacity, this work also serves as an experimental basis for the continued development of dynamic collimators, which has been the subject of recent focus for the DCS using Monte Carlo methods to design focused collimators 28 . Additionally, the activation of positron‐emitting nuclides is also non‐negligible and should be considered when designing the encapsulation of a clinical system.…”
Section: Discussionmentioning
confidence: 99%
“…Hyer et al 12 provided a novel concept of dynamic collimation system (DCS) for penumbra reduction in spot scanning proton therapy. This work was continued by Geoghegan et al 20 who conducted an MC study regarding the design of focused DCS. They found that the focused DCS design reduced dose at the collimated edge as compared to the unfocused collimated devices.…”
Section: Introductionmentioning
confidence: 99%